New concept in animal production with special reference to tropical conditions - A.J. Smith (Hemera Zoa, 1988)
Animals are kept for many purpose throughout the world, thus discussing all the new concepts that could be applied to them is a daunting task. To this consideration must be added the fact thaht most new concepts arise in the developed parts of the world where the constraints to animal production are very different to those in tropical countries. In the former areas various developments have resulted in an over production of many animal product and as a consequence techiques that result in increased production are no longer in vogue.